AN ANALYSIS ON LEARNING STRATEGIES OF SUCCESSFUL ENGLISH LEARNERS - Jannah, Wilda; Wardah, Wardah (Journal of English Education Program, 2022)
This research aimed to describe language learning strategies used by the science 4 students whose English scores of 80 and above. The subject of this study was the successful English learners from the Eleventh Grade of Science 4 Students in SMAN 05 Pontianak. They are 10 students from Science 4. The design of this research was a case study. The data were collected through a questionnaire to determine the students"™ English learning strategies and interview guidelines to get detailed information on English learning strategies used by successful students. The result of the analysis showed, the strategy implemented by the students had improved their English skills. Each student had their distinctive ways and styles in English learning strategies. There were six types of learning strategies used by the students include direct study. The direct study covers memory, cognitive, compensation, and the indirect study covers metacognitive, affective, and social strategy. The findings show that the most dominant strategy used by the students was an indirect strategy rather than a direct strategy. The use of indirect strategies includes metacognitive, affective, and social strategy as shown by the questionnaire mean score at 4,25. Further, the use of direct strategies, including memory, cognitive, and compensation strategy as shown by the questionnaire mean score at 3,91.